Предмет: Математика,
автор: lol1159
ребят ришите плиз очень надо
Приложения:
Ответы
Автор ответа:
0
Из первого выразим x:
x=6-2y
Подставим во второе:
2(6-2y)+y=3
12y-4y+y=3
12-3y=3
-3y=-9
y=3
Подставим y в уравнение :
x=6-2y
x=6-2*3
x=6-6
x=0
Ответ:(x;y)=(0;3)
x=6-2y
Подставим во второе:
2(6-2y)+y=3
12y-4y+y=3
12-3y=3
-3y=-9
y=3
Подставим y в уравнение :
x=6-2y
x=6-2*3
x=6-6
x=0
Ответ:(x;y)=(0;3)
Похожие вопросы
Предмет: География,
автор: Аноним
Предмет: Химия,
автор: dababy96
Предмет: Биология,
автор: zibrohim70
Предмет: Биология,
автор: dilya57
Предмет: Обществознание,
автор: dinaesenina01010